2015
DOI: 10.2176/nmccrj.2014-0028
|View full text |Cite
|
Sign up to set email alerts
|

Dural Arteriovenous Fistula of the Transverse and Sigmoid Sinus Manifesting Ascending Dysesthesia: Case Report and Literature Review

Abstract: Cases involving intracranial dural arteriovenous fistulas (AVFs) with spinal perimedullary venous drainage exhibit variable presentations, which results in delayed diagnoses. We describe a case of a 66-year-old female with a transverse-sigmoid sinus dural AVF with spinal perimedullary venous drainage who developed dysesthesia and hypalgesia that ascended from the peripheral lower extremities. Sixty cases of intracranial dural AVFs resulting in myelopathy have been reported, and an absence of brainstem signs si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…Interestingly, we found that only 9% of patients had brainstem signs, whereas El Asri and colleagues reported their presence in one-third of the patients [ 10 ]; this discrepancy may be due to the different definition of “brainstem signs” between the studies. It was also found that patients presenting with brainstem signs tended to have a shorter time to reach a correct diagnosis (see the “Diagnostic delay” section), which is consistent with current literature [ 11 ]. This may be because patients with brainstem signs are often mistaken for having a stroke and are promptly admitted to the emergency room.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Interestingly, we found that only 9% of patients had brainstem signs, whereas El Asri and colleagues reported their presence in one-third of the patients [ 10 ]; this discrepancy may be due to the different definition of “brainstem signs” between the studies. It was also found that patients presenting with brainstem signs tended to have a shorter time to reach a correct diagnosis (see the “Diagnostic delay” section), which is consistent with current literature [ 11 ]. This may be because patients with brainstem signs are often mistaken for having a stroke and are promptly admitted to the emergency room.…”
Section: Discussionsupporting
confidence: 88%
“…Although several studies have drawn the same conclusion in the past, our study managed to statistically support this hypothesis. In contrast, another study by Kamio et al did not find a correlation between disease duration and prognosis, but did emphasize the importance of prompt and accurate diagnosis for improving symptoms and avoiding poorer outcomes (see the “Outcome” section) [ 11 ]. Of note, in the past some authors reported that even paraplegia can be reversible if the fistula is treated before the occurrence of ischemic and gliotic changes, pointing out the importance of early diagnosis and treatment [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TSS DAVFs can reverse the blood flow of all neighboring superficial and deep venous structures, including the TSS, superior sagittal sinus (SSS), superior petrosal sinus, basal vein of Rosenthal, the vein of Labbé, and cortical and deep medullary veins, which causes brain venous hypertension 41, 44, 45. Even the venous reflux can proceed to the brainstem and medulla veins 46, 47. Therefore, for TSS DAVFs, supratentorial, infratentorial, brainstem and spinal drainage must be evaluated 43, 47.…”
Section: Angioarchitecture and Gradementioning
confidence: 99%
“…Even the venous reflux can proceed to the brainstem and medulla veins 46, 47. Therefore, for TSS DAVFs, supratentorial, infratentorial, brainstem and spinal drainage must be evaluated 43, 47. Under idiopathic intracranial hypertension, the cortical and intramedullary vessels can become tortuous and ectatic 32, 44.…”
Section: Angioarchitecture and Gradementioning
confidence: 99%